Photoluminescence Quenching of Nanocomposite Materials Used for Organic Solar Cells - Thao, Tran Thi; Chung, Do Ngoc; Dinh, Nguyen Nang; Truong, Vo Van (Communications in Physics, 2014)
In this work, we have studied the photoluminescence (PL) quenching of two polymeric composites, poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene] (MEH-PPV) and poly(3-hexylthiophene) (P3HT) in presence of nc-TiO\(_2\) particles by PL- spectroscopy. PL quenching values are 19.2\(%\) and 45.5\(%\), for MEH-PPV+nc-TiO\(_2\) and P3HT+nc-TiO_2, respectively. The obtained results on the relationship of PL quenching and photoelectrical efficiency (PCE) of an OSC showed that the quenching coefficient of a semiconducting polymer can be considered as apreliminarycriterion for choosing an appropriate polymeric composite being used for OSC preparation. Under illumination of solar energyof 56 mW/cm\(^2\), P3HT+TiO\(_2\) based OSC possess FF, V_OC, J_SC and PCE of 0.64, 0.243 V, 1.43 mA/cm\(^2\) and 0.45\(%\), respectively.